Cenários econômicos e ambientais na Amazônia: o impacto da bioeconomia e políticas de desmatamento zero - Vitor da Silva Marinho (2024)
Faced with climate change, a growing global challenge, this dissertation investigates the role of the bioeconomy in the Amazon. The study focuses on projecting the economic impact and land use changes related to the adoption of zero deforestation policies combined with the growth of sectors linked to the bioeconomy in the Amazon between 2020 and 2040. To this end, the REGIA Computable General Equilibrium model was used to simulate economic and environmental scenarios. The results indicate that, despite a projected decrease in production in the bioeconomy sectors, their contribution remains marginal in the Amazon’s sectoral structure. However, the simulations indicate a significant net reduction in deforestation, around 9.83 million hectares avoided in the Legal Amazon by 2040. Although the bioeconomy is not enough on its own to mitigate climate change, it is a promising alternative in certain states of the Amazon, contributing to both the local economy and environmental conservation.